2021 Update on airway management from the Anaesthesia Continuing Education Airway Management Special Interest Group. Issue 4 (July 2021) - Van Zundert, André AJ; Endlich, Yasmin; Beckmann, Linda A; Bradley, William PL; Chapman, Gordon A; Heard, Andrew MB; Heffernan, Drew; Jephcott, Christopher GA; Khong, Geraldine LS; Rehak, Adam; Semenov, Richard A; Stefanutto, Tiscia B; et al.
Airway Management is the key for anaesthetists dealing with patients undergoing diagnostic procedures and surgical interventions. The present coronavirus pandemic underpins even more how important safe airway management is. It also highlights the need to apply stringent precautions to avoid infection and ongoing transmission to patients, anaesthetists and other healthcare workers (HCWs). In light of this extraordinary global situation the aim of this article is to update the reader on the varied aspects of the ever-changing tasks anaesthetists are involved in and highlight the equipment, devices and techniques that have evolved in response to changing technology and unique patient and surgical requirements.